Active disturbance rejection based trajectory linearization control for hypersonic reentry vehicle with bounded uncertainties. (January 2015) - Shao, Xingling; Wang, Honglun
Abstract: This paper investigates a novel compound control scheme combined with the advantages of trajectory linearization control (TLC) and alternative active disturbance rejection control (ADRC) for hypersonic reentry vehicle (HRV) attitude tracking system with bounded uncertainties. Firstly, in order to overcome actuator saturation problem, nonlinear tracking differentiator (TD) is applied in the attitude loop to achieve fewer control consumption. Then, linear extended state observers (LESO) are constructed to estimate the uncertainties acting on the LTV system in the attitude and angular rate loop. In addition, feedback linearization (FL) based controllers are designed using estimates of uncertainties generated by LESO in each loop, which enable the tracking error for closed-loop system in the presence of large uncertainties to converge to the residual set of the origin asymptotically. Finally, the compound controllers are derived by integrating with the nominal controller for open-loop nonlinear system and FL based controller. Also, comparisons and simulation results are presented to illustrate the effectiveness of the control strategy. Highlights: A novel composite control law is proposed for attitude tracking problem of HRV. With known model information, LESO is constructed to estimate the uncertainties. The capability in disturbance rejection and fewer energy consumption is assured. The comparative study is carried out to demonstrate the superiority over other methods.